Kunci Keberhasilan Pengajar Firman Allah: Teladan Musa bagi Guru PAK Masa Kini - Halawa, Arismawati; Gulo, Jeni Murni; Waruwu, Yurniwati; Tapilaha, Sandra Rosiana (Jurnal Riset Rumpun Agama dan Filsafat, 2025)
This article examines the exemplary life of Moses as the key to the success of teaching the word of God and its relevance for Christian Religious Education (PAK) teachers today. Moses is not only known as a prophet and leader of the Israelites, but also as a teacher with high integrity, who relies on God in every aspect of his ministry. Character values ​​such as gentleness, loyalty, dependence on God, and humility are the main attributes that make Moses a figure worthy of emulation. Using a descriptive qualitative method through literature study, this article highlights the importance of a teacher's spiritual life in supporting the effectiveness of teaching the Christian faith. PAK teachers are not enough to just master the cognitive and pedagogical aspects, but need to be living representatives of the teachings they convey. By emulating Moses, PAK teachers are expected to be able to build teaching that is not only informative, but also transformative and inspiring in forming a faithful and responsible generation.